RANCANGAN PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN KERJA SAMA SISWA KELAS IV SEKOLAH DASAR - Oneng Siti Rukoyah, - (2020)
Penelitian ini dilatar belakangi oleh rendahnya kemampuan kerja sama siswa kelas IV di salah satu SD Negeri di Kota Bandung. Hal tersebut dikarenakan guru dalam melaksanakan kegiatan pembelajaran di kelas masih bersifat teacher centered sehingga siswa kurang aktif dalam mengikuti pembelajaran. Penelitian dilakukan untuk mendeskripsikan rancangan pembelajaran kooperatif tipe STAD (Student Team Achievement Division) di kelas IV Sekolah Dasar dan diharapkan dapat meningkatkan kemampuan kerja sama siswa melalui lima tahapan yaitu penyajian materi, kegiatan kelompok, kuis, skor kemajuan dan penghargaan kelompok. The metdod used ini this research is the Delphi method. Data cllection techniques in research using a questionnaire Validated by two exsperts. Data processing and data analysis used is qualitative data analysis. The percentage of design feasibility in this study was 81-100%, expert validation was carried out in two rounds. The percentage in the first round of validation results from expert I showed 80.49% in the feasible category and the results of the validation by expert II showed 97.56% in the very feasible category. Whereas in the second round the percentage of the results of the two experts showed 100% with a very feasible category. Based on the results of research with two rounds of expert validation, it shows that the STAD (Student Team Achievement Division) type cooperative learning design can improve the cooperation ability of fourth grade elementary school students. Keywords: Learning Design, Cooperative Learning, STAD, Cooperation Ability.